Regulation of the rabbit ileal brush-border Na+/H+ exchanger by an ATP-requiring Ca++/calmodulin-mediated process. - Rood, R P (1988)
Brush-border vesicles purified from rabbit ileal villus cells were used to evaluate how Ca++/calmodulin (CaM) regulates the neutral linked NaCl absorptive process, part of which is a Na+/H+ exchanger. After freezing and thawing to allow incorporation of macromolecules into the vesicles, the effect of Ca++/CaM on brush-border Na+ uptake with an acid inside pH gradient, and on Na+/H+ exchange was determined. Freezing and thawing vesicles with 0.85 microM free Ca++ plus 5 microM exogenous CaM failed to alter Na+/H+ exchange as did the addition of exogenous ATP plus an ATP regenerating system, which was sufficient to elevate intravesicular ATP to 47 microM from a basal level of 0.4 microM. However, the combination of Ca++/CaM plus ATP inhibited Na+ uptake in the presence of an acid inside pH gradient and inhibited Na+/H+ exchange, while Na+ uptake in the absence of a pH gradient was not altered. This effect required a hydrolyzable form of ATP, and did not occur when the nonhydrolyzable ATP analogue, AMP-PNP, replaced ATP. Under the identical intravesicular conditions used for the transport studies, Ca++ (0.85 microM) plus exogenous CaM (5 microM), in the presence of magnesium plus ATP, increased phosphorylation of five brush-border peptides. These data are consistent with Ca++/CaM acting via phosphorylation to regulate the ileal brush-border Na+/H+ exchanger.